Intracellular distribution of lead in the liver and kidney of the rat - Castellino, N. (1969)
Castellino, N., and Aloj, S. (1969).Brit. J. industr. Med.,26, 139-143. Intracellular distribution of lead in the liver and kidney of the rat. The distribution of lead in intracellular fractions of liver and kidney has been studied in rats for nine days after intravenous injection of 100 μg. of lead ((210)Pb) per rat. The radioactivity and the protein nitrogen have been measured in the homogenates and in the nuclei, mitochondria, microsomes, and cell sap. Lead penetrates the cells quickly, being present in all fractions one hour after injection. During the first 72 hours the relative amounts of lead in the different fractions varied, which ruled out the possibility that all the differences could be explained by redistribution after homogenization. The distribution of the metal within the cell probably depends upon differences in the nature and the stability of bonding to intracellular structures. The binding of lead within the mitochondria seemed to be particularly stable, only 24·4% of the radioactivity being removed by washing with 0·25 m sucrose or 0·001 m ethylenediaminetetra-acetate or 0·001 m diethylenetriaminopenta-acetate in 0·25 m sucrose. This finding is discussed in relation to haem biosynthesis within the mitochondrion.